Role of hepatitis B virus X protein in regulating LIM and SH3 protein 1 (LASP-1) expression to mediate proliferation and migration of hepatoma cells - Tang, Renxian (BioMed Central, 2012)
BACKGROUND: Hepatitis B virus X protein (HBx) has been shown to be responsible for the development of hepatocellular carcinoma (HCC) caused by Hepatitis B virus infection. However, its potential effect on the progression of hepatocellular carcinoma remains yet unclear. LIM and SH3 protein 1 (LASP-1), a focal adhesion protein, is expressed in an up-regulation manner in the HCC tissues. LASP-1 plays an important role in the regulation of proliferation and migration of HCC. In this study, we investigated the effect of LASP-1 involved in HBx-related tumor progression. METHODS: LASP-1 levels in the HBx stable transfected HepG2 and Huh-7 cells were detected by RT-PCR and western blot analysis. The cellular localization of LASP-1 was assessed by immunofluorescence analysis. The activity of phosphatidylinositol 3-kinase (PI3-K) pathway was demonstrated by western blot assay. The HBx-expressing cells were transfected with specific small interference RNA (siRNA) against LASP-1. The proliferation and migration ability of cells were evaluated by cell viability assay and plate clone formation assay. The migration ability of cells was detected by transwell assay and wound healing assay. RESULTS: RT-PCR and western blot analysis indicated the expression of LASP-1 was increased in the stable HBx-expressing cells compared with the control cells. Immunofluorescence study revealed that the distributions of LASP-1 in HepG2-HBX cells were mainly in pseudopods and the cytoplasm while they were mainly localized in the cytoplasm of HepG2-Mock cells. The cellular localizations of LASP-1 in Huh-7-HBX cells were in the perinuclear fractions while they were mainly localized in the cytoplasm of Huh-7-Mock cells. The upregulation of LASP-1 was inhibited after treatment with LY294002, PI3-K pathway inhibitor. Overexpression of LASP-1 in the stable HBx-expressing cells enhanced the proliferation and migration ability of hepatocellular cells. siRNA-mediated LASP-1 knowdown in the stable HBx-expressing cells significantly suppressed hepatocellular cells proliferation and migration. CONCLUSIONS: These results demonstrated that HBx could upregulate LASP-1 through PI3-K pathway to promote the proliferation and migration of hepatoma cells.